Toxic dinoflagellates (Dinoflagellata) the coast of Chiapas , Mexico , Eastern Pacific center (UNED Research Journal, 2015)
In this paper are given to know toxic species with public health importance, samples were obtained during 2010-2012 in the coast of Chiapas, México, by net (20 μm mesh) in vertical hauls (up to 15 m), fixed with Lugol’s solution and studied by light microscope bright field, Twenty-four species were documented to be present in the study área: Gymnodinium (1); Alexandrium (5); Pyrodinium (1); Phalacroma (2); Dinophysis (4);Prorocentrum (4); Karenia (4); Protoceratium (1); Gonyaulax (1); Lingulodinium (1), It was found corresponding with 64-89% of the species from coastal waters of México.
Keywords: Dinoflagellates; red tide; harmful algae; ficotoxins; Chiapas